Titan’s refractory core evolution: Implications for organics in its subsurface ocean - Kelly E. Miller; Mohit Melwani Daswani; Christophe Sotin; Charles S. Cockell; Catherine Neish; Michael J. Malaska; Kendra K. Farnsworth; Conor A. Nixon; Krista M. Soderlund; Peter M. Higgins; Antonin Affholder; Rosaly M.C. Lopes (Icarus, 2026)

Ocean circulation, sea ice, and productivity simulated in Jones Sound, Canadian Arctic Archipelago, between 2003–2016 - Tyler Pelle; Paul G. Myers; Andrew Hamilton; Matthew Mazloff; Krista M. Soderlund; Lucas Beem; Donald D. Blankenship; Cyril Grima; Feras Habbal; Mark Skidmore; Jamin S. Greenbaum (Ocean Science, 2026)
Jones Sound is one of three critical waterways in the Canadian Arctic Archipelago that regulate liquid exchange between the Arctic Ocean and northern Atlantic Ocean. However, to date, no high-resolution ocean circulation model exists to study the recent evolution of Jones Sound, meaning that our understanding of circulation within the sound is based either on temporally and spatially sparse oceanographic observations or on extrapolating conditions within Baffin Bay, which has a more dense observational record. To address this, we develop a high-resolution (1/120°, 0.9 km) Jones Sound configuration of the Massachusetts Institute of Technology general circulation model and perform coupled ocean–sea ice–biological productivity simulations between 2003–2016. We find that circulation through Lady Ann Strait, Fram Sound, and Glacier Strait comprises 71 %, 14 %, and 15 % of the volumetric transport into and out of Jones Sound, with tidal flushing enhancing the magnitude of volumetric transport through Fram Sound. Warming Atlantic Water within western Baffin Bay flows into Jones Sound through Lady Ann Strait, becomes well-mixed, and circulates counterclockwise, encroaching on the terminus of most tidewater glaciers that line the eastern periphery of the sound. Furthermore, we find that sustained atmospheric and oceanic warming drives an 11 % reduction in the 2003–2016 mean summertime sea ice area, decreased wintertime sea ice thickness, and delayed onset of sea ice refreeze in the fall (thus lengthening the amount of time during which Jones Sound is ice-free). Tidal flushing through Cardigan Strait is critical in triggering melt-back of sea ice across northern Jones Sound. Lastly, this decline in sea ice increases light availability and, when coupled with warming of the subsurface waters in Jones Sound, facilitates enhanced primary productivity down to ∼ 21 m depth. While we note that the modeled warming signal in Baffin Bay is overestimated relative to observations, the results presented here improve our general understanding of how this critical waterway might change under continued polar-amplified global warming and underscores the need for sustained oceanographic observations in this region.